CLIENTELISMO Y CONTROL SOCIAL EN UN PROGRAMA MATERNO-INFANTIL DE LA PROVINCIA DE BUENOS AIRES. - Dallorso, Nicolás Santiago (Tempo da Ciência, 2000)
Clientelism can be conceptualized as that social arrangement that is sustained in a dynamic and interactive relation of dependence between actors of different status that adopts the characteristic of an exchange of votes or loyalties by goods or favors. Nevertheless, the social actors involved in these relationships often do not recognize them as bonds of domination due to the very existence of the exchange. The perspective of the social control allows us to realize of the subjective dimension of this process of naturalization. By social control we understand a particular key of interpretation that takes into account the aspects that contribute to the production of what is allowed and what is forbidden, setting up strategies to naturalize and normalize a given social order, whose contents and senses are not pre-defined, but are the object of dispute. This article explores the links between practices of informal social control, social policy and emergency of clientelar relations in the case of the Plan Vida in the province of Buenos Aires. In this respect, the emergence and the instrumentation of the Plan Vida were a relevant factor in the transformation from a dense clientelism towards a fine clientelism. Besides, this transition is juxtaposed with a greater presence of the social brokers in relation to the political brokers in the clientelar practices.